Quality of diabetes care at the largest outpatient clinics in Vilnius - Visockienė, Žydrūnė; Šiaulienė, Laura; Puronaitė, Roma; Šapoka, Virginijus; Kasiulevičius, Vytautas (Acta medica Lituanica, 2016)
Background. Essential data on the quality of diabetes care needed for the development of National Diabetes Programme in Lithuania are lacking. The aim of the study was to assess the quality of diabetes care compared to the local guidelines in Vilnius, Lithuania. Materials and methods. Retrospective data collection covering the period from 2012 to 2013 was performed in 5 Vilnius outpatient clinics assessing process and outcome indicators in type 1 (T1DM) and type 2 diabetes mellitus (T2DM) subjects. Results. In a sample of 1,719 patients (58.9% women, 92.6% T2DM) the annual HbA1c assessment rate was 88.6%. Glycaemic control was significantly better in T2DM compared to T1DM patients: average HbA1c was 7.0 ± 1.4% vs 9.1 ± 1.8% and HbA1c ≤ 7% in 59 vs 9.4%, respectively (p